Technological Nature and Equipment of Laser Welding - Turdiyev Abdurasul Xalilovich; Abdullayev Jo'ra Xudoyorovich (Peerian Journals Publishing, 2022)
This article discusses melting methods, their uniqueness, nature, and technology
Keywords: welding; melting; atom; power